Media and Occupational Aspirations: The Effect of Television on Career Aspirations of Adolescents. Issue 3 (2nd July 2016) - Gehrau, Volker; Brüggemann, Tim; Handrup, Jutta
Abstract : Vocational decisions are important decisions for adolescents. This article takes television effects into account. A literature review for the occupational world in TV programs reveals a strong focus on some occupations as well as small cultivation effects plus learning effects from mediated role models. A secondary analysis of 2 panel waves was undertaken to study the effect of media role models on occupational aspiration. Television usage in a program segment correlated with corresponding aspirations. A process models showed a strong effect of career aspiration in 1 panel wave on related television usage and career aspirations in the following panel wave.